Pengaruh Desain Fasad sebagai Upaya Optimalisasi Karakteristik Bangunan terhadap Iklim (Studi Kasus Komplek Serpong Garden): Penelitian - Irfan Fadilah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Global temperatures and changes in extreme weather patterns require special attention to building facade design as an effort to mitigate and adapt to climate change. Inappropriate facade design can lead to high energy consumption for cooling and heating, as well as increase carbon emissions from the use of this energy. The importance of this innovation is increasingly urgent given the projected increase in urban population and the need for comfortable and energy-efficient buildings in the future. One concrete step in overcoming this challenge is to implement a facade design that is adaptive to the climate and efficient in energy use. This study will analyze the complex in Serpong Garden as a case study to see how facade design can be optimized for climate adaptation. The housing is located in Serpong Garden which is geographically located at 6 '0 - 6 '20 South Latitude and 106 '20- 106 '43 East Longitude which is in a tropical and humid climate. The focus of this study is to meet the conditions of thermal comfort which are influenced by heat radiation, temperature, humidity and air/wind movement. Based on the analysis of the measurement results, it can be concluded that the design of the modern house facade is not optimal in creating thermal comfort conditions inside the room.